VERNACULAR LANGUAGE USED BY STUDENTS IN THEIR DAILY LIFE - Sonia Sonia; Iman Santoso (IKIP Siliwangi, 2023)
This research focuses only on the use of Sundanese language or Indonesian language. The objective of this research is to find out what the languages that usually used by students from class B3 2016Â English Education of IKIP Siliwangi in their daily life (Sundanese language or Indonesian language), the reason students choose the language and use the language. The method that used in this research is descriptive qualitative method. The samples that used in this research were three students from class B3 2016 English Education in IKIP Siliwangi. Instrument that used in this research was interview. The results of this research are two students usually used Sundanese language, but one student usually used Indonesian language. The reason two students choose and use the Sundanese language, because since childhood have been accustomed and more comfortable to use it. The reason one student choose and use Indonesian language, because to be more easily understood by listener and she do not really understand about Sundanese language.Â Keywords:Â Sociolinguistics; Vernacular language; Daily Life